The Effect of Customer Perception Value on Customer Satisfaction on Consumers of Religious Tour Packages in Bekasi-West Java; Purchase Intention as an Intervening Variable - Untari, Dhian Tyas; Khasanah, Fata Nidaul; Timorora Sandha Perdhana; Tulus Sukreni; Basuki Antariksa; Yanuar Farida Wismayanti (Universitas Pendidikan Ganesha, 2024)
In the tour and travel business, creating, improving, and maintaining customer satisfaction is very important considering the increasingly fierce competition. One dimension that affects customer satisfaction is Customer Perceived Value, where companies strive to provide better value than competitors. This study aims to analyze the effect of Customer Perceived Value on Customer Satisfaction with Purchase Intention as an Intervening variable in religious tour package consumers in Bekasi. This study involved 300 tourists who had enjoyed religious tour packages provided by 10 Bekasi-based religious tour package providers, with 30 respondents per religious tour package operator. The data obtained from the results of questionnaires distributed to respondents were then analyzed using statistical methods. Statistical testing on the path analysis model was carried out using the Partial Least Square (PLS) method. The results showed that Customer Perceived Value has a positive and significant influence on Customer Satisfaction. In addition, Customer Perceived Value also has a positive and significant influence on Purchase Intention. This finding shows the importance of Customer Perceived Value in creating customer satisfaction and increasing purchase intent in the context of religious tourism packages in Bekasi. The implications of this research can provide guidance for religious tour package providers in increasing customer satisfaction and obtaining higher purchase intentions.